Life-cycle performance of deteriorated concrete-filled steel tubular (CFST) structures subject to lateral impact - Hou, Chuan-Chuan; Han, Lin-Hai (Thin-walled structures, 2018)
The life-cycle performance of concrete-filled steel tubular (CFST) columns is investigated through numerical modelling. A finite element analysis (FEA) model is established to simulate the performance of deteriorated CFST structures subject to lateral impact. The imposed effects cover a wide range of factors that may deteriorate the mechanical performance of CFST during its life-cycle, which include: construction issues (preload, residual stress, and imperfection), sustained load (axial load from upper structure), environmental aggressiveness (chloride corrosion) and extreme hazard (impact lateral load). The numerical model is stage-by-stage verified against experimental results and shows good accuracy. It is then employed to analyze the performance of CFST column under the coupled effects, including the failure modes, the full-range load-displacement relationship, and the residual compressive strength. Particularly, the effects of the coupled hazards on the loading capacity of the column are compared with the results when the hazards are separately and independently imposed, which highlights the importance of the life-cycle design for the composite structure. Finally, a parametric study is carried out to analyze the influence of salient parameters on the residual compressive strength of CFST subject to the coupled effects. •A framework for life-cycle analysis of CFST, including a FEA model, is developed.•Analysis of CFST subject to long-term load, corrosion and impact is presented.•A parametric study on the residual compressive strength of CFST is presented.